Writing with the Edge of a Knife - Shyam Patel (Canadian Society for Studies in Education, 2022)
In this piece, I think about the notion of writing dangerously, as in writing in a way that considers what it means to write from the margins. Specifically, I am interested in writing that refuses to seek daddy's penchant and that shifts away from getting swallowed by imposter syndrome. Through snippets of a personal narrative, I share my own experiences with those sites of contention and how I reject writing that prescribes to what someone else wants and what academe accepts and values. In other words, I am departing from conventional and traditional writing, and conceiving writing that emerges outside of the norm. In some manner, I have made a vow to enter that space and to never return. It is in my writing where I put that to work, overcoming my fear of writing and showcasing here what it means to write from the site of the wound.